Investment Mindset: Unveiling Behavioral Bias, Enhancing Financial Literacy, and Delving into Risk Perspectives in Stock Investment Decisions - Aisjah, Siti; Djazuli, Atim; Wati, Cicik Retno; Fadhila, Wildan (West Science Business and Management, 2025)
Effective investment decision-making requires rational analysis, but is often influenced by psychological biases such as overconfidence and herding. This study examines the stock investment decisions of Generation Z in East Java, an age group closely tied to technology. The focus is on analyzing investment behavior, particularly the influence of overconfidence and herding bias, as well as the impact of financial literacy, through the mediation of risk perception. The study was conducted on 228 respondents aged 18–25 years who invested in the Indonesian Stock Exchange. Data collection and analysis used the SEM-PLS method through SmartPLS software. The results of the study indicate that risk perception is able to mediate the relationship between herding and overconfidence bias with investment decisions. However, risk perception cannot mediate the relationship between financial literacy and investment decisions. These findings contribute to the understanding of financial behavior, as well as guide Generation Z investors in making wiser investment decisions through a theoretical framework based on risk perception.